Twenty years of Islamic banking literature by Indonesian researchers: A hybrid reviews - Supriani, Indri; Bahril, Muthi Adilah; Pimada, Laila Masruro; Melzatia, Haura Hazimah; Herianingrum, Sri (Faculty of Economics, Universitas Islam Indonesia, 2024)
Purpose – The emergence and growth of Islamic Banking in Indonesia have significantly increased over the past few decades. Consequently, there is a pressing requirement for a thorough examination to analyze the present state of IB literature, including its development and conceptual framework.Methodology – This study utilizes a bibliometric methodology and Systematic Literature Review (SLR), applying content analysis techniques to uncover the intellectual framework of IB literature produced by Indonesian researchers, as documented in the Scopus database. This study utilized 418 articles published between 2003 and 2023, resulting in a total of 418 articles. Data were analyzed using various software applications, including Publish or Perish (PoP), Excel, VOS-Viewer, and Biblioshiny-R.Findings – This study identifies the institutions, authors, journals, and articles that have had the most influence on IB literature published by academics in Indonesia. Additionally, this study sought to uncover patterns of research collaboration within this body of literature. Moreover, this study discovered four main clusters: comparing Islamic and conventional banks, examining the interaction between Islamic banks and their customers, exploring corporate social responsibility (CSR) and accounting practices, and examining the impact of Covid-19 within the context of Islamic banking. Implications – The findings of this study will assist researchers in identifying a range of potential topics for future research that Indonesian researchers can explore.Originality – Applying bibliometrics and SLR methodologies enables this study to comprehensively assess literature development in the IB in Indonesia by incorporating quantitative and qualitative analyses.